Perceived Organizational Support vs. Ethical Leadership: Which Matters More for Employee Commitment in Private Universities? - Nabilah Safitri,; Survival,; Hanif Rani Iswari, (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract. Private universities often face challenges in sustaining employee commitment due to limited resources and growing competition among educational institutions. This study aims to ` and compare the influence of Perceived Organizational Support (POS) and Ethical Leadership on Organizational Commitment among permanent employees, and to assess the moderating role of POS in the relationship between Ethical Leadership and Organizational Commitment. Data were collected from 74 permanent employees of Widya Gama University Malang and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Perceived Organizational Support significantly influences Organizational Commitment, while Ethical Leadership has no significant effect. Furthermore, the moderating effect of POS on the relationship between Ethical Leadership and Organizational Commitment was not statistically significant. These results indicate that, within the context of private higher education institutions, employees’ commitment is more strongly shaped by tangible organizational support systems than by individual ethical leadership traits. Keywords: Perceived organizational support, ethical leadership, organizational commitment, private university employees, PLS-SEM, Widyagama University